Measuring the ‘leaving no one behind’ principle in the European countries: An AROPE-based fuzzy logic approach. - García-Pardo, Francisca; Bárcena-Martín, Elena María; Pérez-Moreno, Salvador Jesús (My University, 2021)
In this paper we present a fuzzy multidimensional approach for the measurement of the `leaving no one behind' principle underlying the Sustainable Development Goals (SDGs) in European countries. In particular, we consider a two-step procedure. First, we compute the degree to which an individual is `left behind' in each speci c dimension. We then propose alternatives to measure the extent to which an individual is `left behind' in a multidimensional setting. We illustrate our proposal taking as a reference the `at risk of poverty or social exclusion' (AROPE) framework (dimensions, indicators and union criteria). The results highlight that although the average `left behind' (LB) level and AROPE are largely consistent across European countries, our fuzzy measure provides valuable additional information, both in individual and aggregate terms, on persons who are further away from those better positioned and how far they are.
Política de acceso abierto tomada de: https://v2.sherpa.ac.uk/id/publication/11428
Keywords: Conjuntos difusos; Pobreza; Unión Europea - Política económica; Fuzzy sets; Multidimensional poverty; AROPE; Left behind